MTHFD1 promoter hypermethylation increases the risk of hypertension - Miao Xu; Jialin Li; Xiaomin Chen; Liyuan Han; Li Li; Yahui Liu (Clinical and Experimental Hypertension, 2019)
Objectives: Methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) plays an essential role in folate-mediated one-carbon metabolism which determines both homocysteine remethylation and de novo thymidylate biosynthesis. Hyperhomocysteinemia is positively associated with essential hypertension. This study aimed to investigate the association of MTHFD1 promoter methylation with essential hypertension. Methods: Using the quantitative methylation-specific polymerase chain reaction (qMSP), the levels of MTHFD1 promoter methylation in 243 essential hypertension patients, 218 age- and gender-matched healthy controls. The relative changes in serum MTHFD1 promoter methylation were analyzed using the 2−ΔΔCt method. The percent of methylated reference (PMR) of MTHFD1 was used to evaluate the MTHFD1 promoter methylation levels. Results: In our current study, the MTHFD1 promoter methylation of hypertensive patients were both higher than the healthy control group (median PMR were 8.97% and 5.69%, respectively, all p < 0.001). Multivariable analysis showed MTHFD1 promoter hypermethylation increase the risk of essential hypertension (OR, 1.336; 95%CI, 1.235–1.446; p < 0.001). The area under the curve (AUC) of MTHFD1 promoter methylation was 0.739 in total patients with essential hypertension. Conclusions: MTHFD1 promoter hypermethylation was a potential biomarker for the diagnosis of essential hypertension.